Sosialisasi Etika Komunikasi Di SD N 086 Bengkulu Utara Desa Sido Luhur, Kecamatan Padang Jaya, Kabupaten Bengkulu Utara - Intan, Dyah Noor; Nasution, Nasution; Permatasari, Keni Diya; Andriyeni, Andriyeni (Jurnal Pengabdian, 2023)
Ethics is a very general thing, meaning that ethics is what every human being must know, in social life, but when it becomes a principle of right and wrong in the behavior of every human being, communication is seen as having multiple meanings and is complex, this is because communication is a social phenomenon that can be interpreted in various ways. Even though the phenomenon of communication remains and does not change, the understanding of this phenomenon can differ from one person to another. Many people don't understand how to carry out good and correct communication ethics in the surrounding environment and the most dominant is among children. Very many children lack ethics among their parents at home and at school. The aim of this community service activity is to provide outreach or counseling to students at SDN 086 North Bengkulu, Sidoluhur village, Padang Jaya District, North Bengkulu Regency so they can understand how to have good ethics. The method used is a form of socialization. This socialization activity was delivered to 50 students of SDN 086 North Bengkulu, Sidoluhur village. The results obtained during community service activities were 1) the participants were enthusiastic about the material provided, as seen from the many questions asked by the participants, 2) In general the participants already knew how to carry out good and correct etiquette. The conclusion of this community service activity is 1) the service participants and all staff of SDN 086 North Bengkulu welcomed this service program. 2) the implementation of the service program went quite well and smoothly and the participants were quite enthusiastic. 3) The staff of SDN 086 North Bengkulu hope that there will be a further service program with another theme to broaden and broaden the students' insight